2021
DOI: 10.1038/s41597-021-00894-y
|View full text |Cite
|
Sign up to set email alerts
|

A resource of lipidomics and metabolomics data from individuals with undiagnosed diseases

Abstract: Every year individuals experience symptoms that remain undiagnosed by healthcare providers. In the United States, these rare diseases are defined as a condition that affects fewer than 200,000 individuals. However, there are an estimated 7000 rare diseases, and there are an estimated 25–30 million Americans in total (7.6–9.2% of the population as of 2018) affected by such disorders. The NIH Common Fund Undiagnosed Diseases Network (UDN) seeks to provide diagnoses for individuals with undiagnosed disease. Mass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 29 publications
(18 reference statements)
0
13
0
Order By: Relevance
“…As a third example, we are showcasing plasma lipidome data from a human reference population presented in Kyle et al [ 22 ], which comprises 136 samples and 302 lipids, mostly identified as molecular species. All patients do not suffer from any diagnosed disease and represent the United States population in terms of age and sex distribution.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…As a third example, we are showcasing plasma lipidome data from a human reference population presented in Kyle et al [ 22 ], which comprises 136 samples and 302 lipids, mostly identified as molecular species. All patients do not suffer from any diagnosed disease and represent the United States population in terms of age and sex distribution.…”
Section: Resultsmentioning
confidence: 99%
“…Prior to uploading the data, reported as peak areas, it was quotient-normalized [ 32 ] and generalized log2 transformed. Healthy human reference population data of the plasma lipidome was taken from Kyle et al [ 22 ]. Unsupported lipid classes, namely Sulfatide and Carnitine, two Endocannabinoids and Co-Enzyme Q10 were removed, and LPE-P was manually added to the lipid class settings file.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations